Antiepileptic activity of four selected Skullcap (Scutellaria) species on mice - Okan Arıhan; Gulderen Yildiz Yilmaz; Mehmet Cicek; Hamdi Demirkol (Van Tıp Dergisi, 2018)
INTRODUCTION: Epilepsy is a common neurological disorder which has different types. Epileptic convulsions are decreasing life quality of patients and can even cause death. Medical treatment of epilepsy includes drugs and surgical interventions. Plant originated substances offers new molecules in this issue. METHODS: In this study we have studied 4 different Skullcap (Scutellatia) species. Methanolic extracts of aerial parts of Scutellaria brevibracteata subsp brevibracteata, S.galericulata, S. megalapsis and S. orientalis subsp pichleri were tested on mice in pentylentetrazolium induced convulsions. Animals were administered 5 days with 200 mg/kg i.p. plant extracts dissolved in physiological saline. Last day they were injected with 80 mg/kg pentylentetrazol. Phenytoin was tested as standard drug. PTZ group was administered solely with pentylentetrazol. RESULTS: Results showed a significant increase in latency to have tonic-clonic convulsions in S.galericulata (532 s) and S. orientalis subsp pichleri (621 s) groups compared to pentylentetrazol group (322 s). Phenytoin prevented such convulsions. No significant difference was found between groups for latency for first myoclonic convulsion and tonic-clonic convulsion period. DISCUSSION AND CONCLUSION: Results of current study indicate an anticonvulsive effect of S. galericulata and S. orientalis subsp pichleri species against pentylentetrazol induced tonic-clonic convulsions. Further studies are needed to determine related molecules from this activity.